The Sudanese Defensive Jihad Against the Rapid Support Forces (Rebels): A Comparative Jurisprudential Study with United Nations Law and the Universal Declaration of Human Rights - Salim, Haitham Balla Abdlla (Journal of Islamic Sciences, 2025)
The primary objective of the research was to determine the Islamic ruling regarding the right of Sudanese citizens and soldiers to defend themselves, their homeland, their property, and their honor in the face of the Rapid Support Forces' (rebels) incursions. The study employed an inductive, analytical, and deductive methodology and included key themes such as the virtue of fighting against aggressors, the obligation to defend one's family or others from assault, and the permissibility of fighting anyone attempting to kill or harm them in self-defense.And the research concluded with important findings, standing on the definition of the rebels and the legitimacy of fighting them, the ruling of rebellion and armed uprising against the state, the conditions for fighting the rebels, and the legitimacy of repelling the rogue forces of the Rapid Support Forces (the rebels). The scholars did not differ in repelling those who intend to rape their own or others' honor, and the permissibility of repelling aggression against property, although it is not obligatory. And whoever intends to attack him with killing, he has the right to defend himself, and the legitimacy of mobilization and the use of barrel bombs when necessary, and the ruling of withdrawing from fighting the Rapid Support Forces (the rebels) and joining other combat units, and this is not called fleeing, which incurs sin. Finally, the research stood on the ruling of leaving the fighting due to a tendency towards peace. And it included recommendations of paramount importance, as the spread of demonstrations and peaceful protests, and then the carrying of arms against the state and its rulers, led the Arab world and the Islamic world in general to a loss that some countries that witnessed those demonstrations are experiencing, and Sudan is the best example.
Keywords: rebellion; rebels; drones; rape; aggressor